2023
DOI: 10.1177/21582440231210372
|View full text |Cite
|
Sign up to set email alerts
|

Association of Gratitude With Individual and Organizational Outcomes Among Volunteers: An Application of Broaden-and-Build Theory of Positive Emotions

Hongcui Yang,
Chuqiao Liang,
Yue Liang
et al.

Abstract: By applying the broaden-and-build theory of positive emotions to the context of volunteering, we investigated how gratitude is associated with individual (subjective well-being) and organizational (volunteer retention) outcomes through the positive thought–action repertoires of prosocial motivation and volunteer engagement. The data of 924 Chinese volunteers (mean age = 35.7 ± 9.1 years, 26.2% males) from voluntary organizations were collected through an online survey. The indirect effects of gratitude on subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
(114 reference statements)
0
1
0
Order By: Relevance
“…According to the theory's premise, gratitude is a positive emotion that broadens people's outlook, making them more likely to notice and appreciate positive aspects of their lives, and fostering a broader and more inclusive perspective. Over time, the experience of gratitude is believed to help people build personal resources, develop positive coping mechanisms and reinforce patterns of positive thinking (Xiang & Yuan, 2021;Yang et al, 2023). Indeed, research has indicated that cultivating a sense of gratitude can help shift one's focus away from negativity and pessimism and promote a more positive and contented mindset (Portocarrero et al, 2020).…”
Section: Gratitudementioning
confidence: 99%
“…According to the theory's premise, gratitude is a positive emotion that broadens people's outlook, making them more likely to notice and appreciate positive aspects of their lives, and fostering a broader and more inclusive perspective. Over time, the experience of gratitude is believed to help people build personal resources, develop positive coping mechanisms and reinforce patterns of positive thinking (Xiang & Yuan, 2021;Yang et al, 2023). Indeed, research has indicated that cultivating a sense of gratitude can help shift one's focus away from negativity and pessimism and promote a more positive and contented mindset (Portocarrero et al, 2020).…”
Section: Gratitudementioning
confidence: 99%